2010
DOI: 10.1007/s10562-010-0336-x
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Sulfur and Oxygenated Compounds of Supported Pd, Pt, Rh, Ru Catalysts

Abstract: The poisoning resistance to sulfided and oxygenated compounds of some VIII Group PYGAS selective hydrogenation catalysts based on metals was assessed. Low content alumina supported Rh, Pd, Ru and Pt catalysts (0.35 wt%) were prepared from chlorided precursors. In the case of the palladium catalysts a nitrogenated precursor was also used. The catalysts were mainly assessed in the catalytic test of selective styrene hydrogenation in the presence or absence of known poisons. Model feedstocks spiked with thiophene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 38 publications
1
52
0
Order By: Relevance
“…In previous works we have reported that monometallic Pd catalysts prepared from chlorinated precursors are more active, sulfur and oxygen resistant than similar Pd catalysts prepared from nitrogenated salts or other noble metal catalysts (Pt, Ru and Rh) [6,8]. We have also reported that when Pd is supported over composite organic-inorganic supports, the resulting catalysts prove to be highly active for the selective hydrogenation of styrene [9].…”
Section: Introductionmentioning
confidence: 79%
“…In previous works we have reported that monometallic Pd catalysts prepared from chlorinated precursors are more active, sulfur and oxygen resistant than similar Pd catalysts prepared from nitrogenated salts or other noble metal catalysts (Pt, Ru and Rh) [6,8]. We have also reported that when Pd is supported over composite organic-inorganic supports, the resulting catalysts prove to be highly active for the selective hydrogenation of styrene [9].…”
Section: Introductionmentioning
confidence: 79%
“…These species would have the formula, Pd η+ Cl x O y with 0 < η < 2. 6 The bimetallic PdNiN and NiNPd catalysts had a peak at 333.5 ± 0.3 eV that according to some reports would have a higher availability of electrons, i.e. they would be species Pd δ-(with δ < 0).…”
Section: Catalysts Characterizationmentioning
confidence: 96%
“…6 As seen in Table 3 , Lewis acid sites). Besides the lower thioresistance of PdNiN and NiNPd would be related to the amount of exposed Pd δ-species (Lewis basic sites) that promote a strong adsorption of the poison and thus an increase of the blocking of active sties.…”
Section: Catalytic Testmentioning
confidence: 99%
See 2 more Smart Citations